2017
DOI: 10.1021/acs.jafc.7b01396
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenoid Components from Oak Heartwood (Quercus robur) and Their Potential Health Benefits

Abstract: For centuries oak wood (Quercus robur) has been used in aging of wines and spirits, which is based on pleasant flavors given to beverages by phenolics transferred to the liquid during the maturation process. Other metabolites, such as triterpenoids, can also be released. Searching for extractable triterpenoids in oak heartwood, 12 new, 1-12, and five known, 13-17, oleanane types were isolated and characterized. Their cytotoxicities were tested against cancer cells (PC3 and MCF-7) and lymphocytes. Breast cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
3
22
0
3
Order By: Relevance
“…Using HRESIMS and 1D/2D NMR experiments, Gammacurta et al [ 89 ] screened EtOAc extracts from the Quercus petraea heartwood for phytochemical investigations and isolated eight new triterpenoids (1−8) ( Figure 2(b) ) and two known functionalized triterpenoids. Posteriorly, Perez et al [ 90 ] in their study, identified 12 new triterpenoids, 1−12 ( Figure 2(c) ), and five known oleanane types which showed cytotoxicity activity against cancer cells (PC3 and MCF-7) and lymphocytes.…”
Section: Phytochemicalsmentioning
confidence: 99%
See 3 more Smart Citations
“…Using HRESIMS and 1D/2D NMR experiments, Gammacurta et al [ 89 ] screened EtOAc extracts from the Quercus petraea heartwood for phytochemical investigations and isolated eight new triterpenoids (1−8) ( Figure 2(b) ) and two known functionalized triterpenoids. Posteriorly, Perez et al [ 90 ] in their study, identified 12 new triterpenoids, 1−12 ( Figure 2(c) ), and five known oleanane types which showed cytotoxicity activity against cancer cells (PC3 and MCF-7) and lymphocytes.…”
Section: Phytochemicalsmentioning
confidence: 99%
“…Perez et al [ 90 ] studied the cytotoxic activity of 17 triterpenoids isolated from oak heartwood of Quercus robur against human prostate cancer (PC3) and human estrogen-dependent breast adenocarcinoma (MCF-7) cell lines and lymphocytes derived from human peripheral blood. The obtained results demonstrate that breast cancer cells (MCF-7) were the most affected by triterpenoids, with roburgenic acid, being the most active compound (IC50 = 19.7 μ M).…”
Section: Pharmacological Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Taken together, 2190 metabolites from AMM were annotated by our integrated bioinformatics pipeline (Additional file 3). Among them, the most abundant are Terpenoids (254), followed by Flavonoids (101), Alkaloids (97), Phenylpropanoids (57), and Fatty acids related compounds (35) ( Table 1). We found an unprecedented number of metabolites from AMM, for which we have increased the number of annotated metabolites by an order of magnitude over previous studies.…”
Section: Resultsmentioning
confidence: 99%